2022
DOI: 10.7717/peerj.14503
|View full text |Cite
|
Sign up to set email alerts
|

Stigmatization towards healthcare personnel during the first COVID-19 wave in Central and Northern Mexico

Abstract: The evidence all over the world shows an alarming increase in the stigmatization of health personnel during the COVID-19 pandemic. We sought to explore possible psychological factors that help explain the disposition to stigmatize health personnel in the central and northern regions of Mexico. Two studies explore possible psychological factors to explain the disposition to stigmatize healthcare personnel (HP) in Mexico during the COVID-19 pandemic. In study one, 520 participants responded to three instruments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Participants from our study expressed that the stigma was mainly rooted in the fear of infection. This is supported by a quantitative study from Mexico that showed perceived risk of contagion to be the main predictor of stigmatization [27]. Another study among Nigerian community HCWs also showed that fear of infection resulted avoiding behaviour by community members which led to underutilization of health services [28].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Participants from our study expressed that the stigma was mainly rooted in the fear of infection. This is supported by a quantitative study from Mexico that showed perceived risk of contagion to be the main predictor of stigmatization [27]. Another study among Nigerian community HCWs also showed that fear of infection resulted avoiding behaviour by community members which led to underutilization of health services [28].…”
Section: Discussionmentioning
confidence: 89%
“…We interviewed 32 females and 21 males between the age of 23 and 64 years (on average 31 years). Interviewees from the Philippines were on average 43 years old and thus older compared to the other countries (average ranging from [27][28][29][30][31][32][33]. Interviewees worked as nurse assistants (n = 9), nurses (n = 25), or physicians (n = 18) on COVID-19 departments in urban (n = 45) or rural (n = 3) hospitals.…”
Section: Participant Characteristicsmentioning
confidence: 99%